Development of a Bioassay for Pulmonary Cell Production of Fibrogenic Factors - R. Reist; K. Bryner; P. Wearden; J. Blackford; K. Vrana; V. Castranova; R. Dey (The National Institute for Occupational Safety and Health (NIOSH), 1992)
"Summary: Fibroblast proliferation and enhancement of collagen synthesis are key steps in the development and progression of pulmonary fibrosis. The current investigation presents a fibroblast proliferation assay to detect the release of competence factors from pneumocytes. The specific objective of this study was to define cell culture conditions for fibroblasts that would allow selective detection of competence factors in test media. The results indicate the following: (a) fibroblasts should be cultured for 2 days in plasma-free medium rather than 2% plasma to assure complete quiescence; (b) 1% plasma was optimum for producing progression activity for the bioassay of a competence factor, while 0.5% plasma did not produce sufficient progression activity (yielding false negatives) and 2% plasma often contained significant competence activity (yielding false positives); and (c) fresh plasma should be used since the progression activity of plasma was adversely affected by freezing and thawing. Under these conditions, this bioassay can be employed with either rat or human lung fibroblasts to detect competence factors such as platelet-derived growth factor (PDGF), at levels as low as 25 ng/ml.Fibrotic lung disease, as a consequence of occupational exposure to silica dust. is characterized by the development of concentric hyalinized nodular lesions in the lung and the progressive loss of pulmonary diffusion capacity. Proliferation of pulmonary fibroblasts and enhanced synthesis of collagen by these pneumocytes have been shown to be key steps in the development of chronic silicosis ( 1 ). The regulation of lung fibroblast proliferation by cytokines released from alveolar macrophages may be an important pathogenetic mechanism in the development of the fibrotic process (2). Some cytokines stimulate fibroblast proliferation by activating specific phases of the cell cycle (3,4). In particular, platelet-derived growth factor (PDGF) promotes fibroblast proliferation by inducing the movement of quiescent (G0 ) cells into the G1 phase of the cell cycle (5). Insulin-like growth factor (IGF) and transforming growth factor-P (TGF-P). on the other hand, regulate the rate of transition of fibroblasts from G 1 into the S phase (5,6). These two classes of cytokines have been termed competence and progression factors, respectively. One approach used to examine the release of cytokines from macrophages is the fibroblast proliferation assay in which quiescent fibroblasts are exposed to culture supematants from macrophages exposed to various stimuli. In most of these assays, the supernatant contains fetal calf serum (FCS), which provides the competence factor(s) necessary to facilitate the proliferation of fibroblasts (7-9). Recently, a fibroblast proliferation assay using platelet-poor .plasma [lacking competence factor(s)] as a substitute for FCS bas been described (I 0, 11 ). In this assay, the release of a competence-inducing PDGF-like growth factor from rat and human macrophages can be distinguished from other cytokines that act as progression factors."